CSF glucose tracks regional tau progression based on Alzheimer's disease risk factors. Issue 1 (24th August 2020) - Pappas, Colleen; Klinedinst, Brandon S.; Le, Scott; Wang, Qian; Larsen, Brittany; McLimans, Kelsey; Lockhart, Samuel N.; Allenspach‐Jorn, Karin; Mochel, Jonathan P.; Willette, Auriel A.; ,
Abstract: Introduction: Glucose hypometabolism and tau formation are key features of Alzheimer's disease (AD). Less is known about the relationship between fasting glucose and regional tau accumulation. Methods: Cerebrospinal fluid (CSF) glucose was linearly regressed on regional tau (flortaucipir) among 169 Alzheimer's Disease Neuroimaging Initiative (ADNI3) participants. Flortaucipir uptake was examined by Braak stages and regions of interest (ROIs). Interactions were explored between CSF glucose and AD risk factors including regional amyloid beta (Aβ), sex, Apolipoprotein E ε4 ( APOE ε4) status, AD parental family history (AD FH), and cognitive impairment (CI). Results: Interactions found higher CSF glucose tracked less tau in ROIs or Braak stages I/II (women, APOE ε4+, regional Aβ), III/IV (AD FH+, regional Aβ), and V/VI (AD FH+). CI drove Braak III‐VI associations. Discussion: Among women and APOE ε4 carriers, higher CSF glucose tracked less early‐stage tau. Higher CSF glucose may reflect compensation against tau spreading in CI, Aβ+, or AD FH+.